Desain dan Penataan Kelas Aman Bencana pada Madrasah Ibtidaiyah Negeri (MIN) 3 Pacitan: - - diana diana rendrarini (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2023)
Earthquakes are one of the main threats of concern in Indonesia, which has been successfully recorded which also shows that an average of ten earthquakes occur every year which cause considerable damage in Indonesia. This study on the design of disaster-safe buildings at MIN 3 in Pacitan Regency uses a quantitative descriptive method. With the design of a disaster-safe school, it is hoped that Pacitan 3 Public Madrasah Ibtidaiyah (MIN) can be even more prepared in dealing with disasters. Meanwhile, for a better understanding of disaster-safe schools, it is necessary to hold disaster simulations every certain period at school